SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/135073-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rate Allocation: Combining Transient Well Flow Modeling and Data Assimilation

Abstract: This paper presents an approach for rate allocation for individual wells by combining a transient well flow model and the ensemble Kalman filter. Specifically, we aim to utilize available high frequency measurements of pressure and temperature, focussing particularly on the early time period after changing influx conditions. The transition between two steady state flow periods implies natural excitation of the well flow, and during this phase an individual sensor experiences a golden age compared to the single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that in contrast with optimization algorithms, the Kalman filtering is more capable of dealing with sufficiently noisy data. Lorentzen et al [10] combined transient downhole pressure and temperature data in a soft-sensor based on the ensemble Kalman filter and a transient wellbore model. They have indicated that changing influx conditions can be detected from downhole temperature observations located close to influx zones.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in contrast with optimization algorithms, the Kalman filtering is more capable of dealing with sufficiently noisy data. Lorentzen et al [10] combined transient downhole pressure and temperature data in a soft-sensor based on the ensemble Kalman filter and a transient wellbore model. They have indicated that changing influx conditions can be detected from downhole temperature observations located close to influx zones.…”
Section: Introductionmentioning
confidence: 99%
“…With the need of monitoring of down-hole multi-phase flow and the increase in number of wells equipped with PDHGs, DTS and DPS to acquire real-time down-hole pressure and temperature measurements, interest are growing to use these measurements to estimate the down-hole multi-phase flow by means of soft sensing (Naevdal et al 2001;Leskens et al 2008;de Kruif et al 2008;Lorentzen et al 2010). Naevdal et al (2001) has performed uncertainty analysis to search for the optimal location and type of sensors to be used for estimating the inflow profile of the well having three producing zones using steady-state three-phase flow simulator.…”
Section: Introductionmentioning
confidence: 99%
“…These rates are then allocated to individual wells based on either well rate test and downtime or well rate models supported by real time data. The relative discrepancy between the measured fieldwide rate and the summation of all calculated rates from the individual wells is called allocation factor or field factors (Lorentzen et al, 2010) for oil, water, and gas, respectively. The allocated well rates are obtained by adjusting the calculated rates by the allocation factors.…”
Section: Introductionmentioning
confidence: 99%